Characterization on a-SiC thin film by X-ray diffraction, Raman spectroscopy and infrared radiation spectroscopy / Nur Syuhada Mohd Shahril - Mohd Shahril, Nur Syuhada (2010)
In this research, silicon carbide thin films were initially deposited by a home-build HW chemical vapors deposition (CVD) system at low temperatures 250 °C and deposition rates of 0.12 cm/s. The specific problem statement in this study is to enhance the structural properties of a-SiC thin film through annealing process. In order to study the effects of annealing on the structural properties of a-SiC thin film, it was annealed from100 °C to 400 °C. Studies were done through characterizations by using the X-ray diffraction spectrum (XRD), Raman spectroscopy and also the Fourier Transform Infrared Radiation (FTIR). The analysis through XRD shows the crystallite size of a-Si Chad increased due to increasing annealing temperature. From Raman spectroscopy analysis, it was found that the annealing temperature between 100 °C to 400 °C does not affect the carbon compound in the thin film. Lastly, FTIR analysis shows changes only occur at the first anneal temperature which is at 200 °C. After that there is no change in crystallite structure when anneal at 300°C until 400°C. This is because the compound of Si is stretched resulting in increased crystallite size.